Building Opportunities and Organizational Strength for SMEs Transformation (BOOST): A Community Service Model for Cooperative Development in Jatisari, Bekasi Using the AHP Method - Tri Hadi Sulistyanto; Indri Putri Utami; Salsa Billah Arianti Suryana; Silmi Rachmawati (Jurnal Sentra Pengabdian, 2025)
The “Koperasi Merah Putih” (KMP), or Red and White Cooperative, is a strategic government initiative mandated by Presidential Instruction No. 9 of 2025. It aims to accelerate the establishment of cooperatives at the village and urban ward levels as a means to strengthen the people’s economy and empower micro, small, and medium enterprises (MSMEs). Jatisari Urban Ward in Jatiasih Subdistrict, Bekasi City, is one of the areas that has implemented the selection of cooperative board members. However, the selection process has so far applied equal weighting across all assessment criteria, without considering their relative importance. This community service programme aims to develop a rational weighting scenario using the Analytical Hierarchy Process (AHP) method. Data were collected through observation and interviews with the selection committee. Eight selection criteria were analyzed through pairwise comparisons by the selection committee (“Tim Formatur”), resulting in a priority weighting that reflects the significance of each criterion in the success of the cooperative. The results show that the relevance of the candidate's presentation to the concept of KMP, as well as the clarity and feasibility of the proposed work programme, have the highest weights. The consistency check yielded a Consistency Ratio (CR) of 6.77%, This weighting model, developed through the BOOST approach, strengthens cooperative governance and supports MSME transformation by promoting an objective and transparent board selection process that can be replicated in other regions